Tuberculous Pneumonia as a Primary Cause of Acute Respiratory Distress Syndrome: A Case Report - Yuliza; Helmia Hasan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Tuberculosis is an uncommon and very rare cause of Acute Respiratory Distress Syndrome.Moreover, it has been associated with poor outcomes with a very high mortality rate (40-80%). The clinicalsymptoms and radiological findings of tuberculous pneumonia that resemble bacterial pneumonia resultin difficulties to decide definitive diagnosis. Case Presentation: A 35-year-old male patient was admittedto hospital with shortness of breath, fever, cough without expectoration. The patient had history of asthmasince childhood. Chest physical examination showed rhonchi and wheezing on both lungs. Initial laboratoryfindings were leucocytosis, granulocytocis, eosinopenia, increased ALT and ALP levels, blood gas analysisrevealed acute respiratory failure. PaO2/FiO2 was 49 mmHg. ECG showed sinus tachycardia and chestX-ray showed consolidation on both lungs. The patient was initially managed for asthma exacerbation andbilateral pneumonia with ARDS. The result of microbiological findings showed acid fast bacilli (AFB)positive. He had been treated with anti-TB first category. Clinical improvement was achieved after 1 week ofanti-TB treatment. Summary: Tuberculous pneumonia with ARDS is a rare case of pulmonary tuberculosis.The diagnosis is established by a prompt and complete examination that lead to optimal treatment withappropriate anti-TB.